2021
DOI: 10.3390/agronomy11030604
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Soybean Lines Adapted to Sub-Saharan Africa Using Single Nucleotide Polymorphism (SNP) Markers

Abstract: Soybean productivity in sub-Saharan Africa (SSA) is less than half of the global average yield. To plug the productivity gap, further improvement in grain yield must be attained by enhancing the genetic potential of new cultivars that depends on the genetic diversity of the parents. Hence, our aim was to assess genetic diversity and population structure of elite soybean genotypes, mainly released cultivars and advanced selections in SSA. In this study, a set of 165 lines was genotyped with high-throughput sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
5
20
2
Order By: Relevance
“…In this study, the PIC values were much lower than previously reported studies in AYB [ 1 , 19 , 21 23 ] which are mainly attributed to the type of markers used because RAD-SNP markers are bi-allelic in nature when compared with multi-allelic markers [ 32 ]. Furthermore, such discrepancy in genetic diversity could also be due to the differences in the studied material and number of applied genotypes as well as markers [ 32 34 ]. However, the PIC values obtained in present study are similar to ones obtained from DArT SNP markers in maize [ 24 ] and sugar beet [ 35 ].…”
Section: Discussioncontrasting
confidence: 68%
“…In this study, the PIC values were much lower than previously reported studies in AYB [ 1 , 19 , 21 23 ] which are mainly attributed to the type of markers used because RAD-SNP markers are bi-allelic in nature when compared with multi-allelic markers [ 32 ]. Furthermore, such discrepancy in genetic diversity could also be due to the differences in the studied material and number of applied genotypes as well as markers [ 32 34 ]. However, the PIC values obtained in present study are similar to ones obtained from DArT SNP markers in maize [ 24 ] and sugar beet [ 35 ].…”
Section: Discussioncontrasting
confidence: 68%
“…The SNP and DArT markers demonstrated a moderate rate of PIC values from 0.01 to 0.375 and 0.0106 to 0.58, respectively. Other crop species, such as maize and soybean, have generated similar values of moderate PIC scores for genome-wide markers such as SNP and DArT [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, drought is a major environmental threat to agriculture sustainability in the world which affects physiological plant growth and performance [1,2]. Nonetheless, both pre-and post-flowering drought stress limits crop yield, though post-flowering drought stress is a major concern for sorghum farmers in Tanzania where it occurs when plants are at the grain filling stage and critical for the determination of yield performance [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the diverse DNA-based markers, SNPs markers clearly detect the existing polymorphism among genotypes, including in sorghum [20,21]. Compared with electrophoresis systembased traditional SNP markers, Kompetitive allele-specific PCRs (KASP) are useful because of low genotyping error rate and amenability to automation that may complement direct phenotyping under field conditions resulting in short breeding cycles in complement with conventional breeding method [2,22]. Additionally, codominant nature of KASP markers facilitates identification of favourable alleles in heterozygous conditions for the introgression of traits through MABC which are either governed by dominant or recessive gene action [23][24][25].…”
Section: Introductionmentioning
confidence: 99%